In irradiation chimeras, K or D regions of the chimeric host, not of the donor lymphocytes, determine immune responsiveness of antiviral cytotoxic T cells - Zinkernagel, RM (The Rockefeller University Press, 1978)
The H-2 haplotype of the chimeric host determines the responder phenotype of maturing T cells. Spleen cells of chimeric mice formed when (K(k) nonresponder to D(b) × K(b) responder to D(b) plus vaccinia)F(1) bone marrow cells were used to reconstitute K(b)D(b) (C57BL/6 D(b) responder) irradiated recipients generated high levels of D(b) plus vaccinia virus-specific cytotoxic T cells. The same stem cells used to reconstitute K(k)D(b) (B10.A (2R) D(b) nonresponder) irradiated recipients resulted in spleen cells that responded well to K plus vaccinia, but responsiveness to D(b) was low. A generally low response to D(k) plus vaccinia, which seems to be regulated by D(k), was confirmed in chimeras. Thus, K(d)D(d) (D(d) plus vaccinia responder) stem cells differentiating in a K(d)D(k) chimeric host failed to generate a measurable response to D(k) plus vaccinia. In contrast, stem cells from K(d)D(k) (D(k) plus vaccinia low responders) differentiating in a K(d)D(d) (K(d) and D(d) high responders to vaccinia) host do generate responsiveness to D(d) plus vaccinia. These results indicate that in chimeras, the Ir phenotype is independent of the donor T cell’s Ir genotype, and that thymic selection of a T cell’s restriction specificity for a particular H-2 allele of the chimeric host also defines that T cell’s/r phenotype.